THE OUTCOME OF THE 2012 PROMTION OF PEA VEGQ ETABLE VARIETIES OF VNIISSOK BREEDING - S. M. Sirota (Овощи России, 2015)
A brief description  of weather  conditions  in 2012 is shown in the areas of pea production.  The reaction  of pea varieties of VNIIS, SOK breeding   at growing  in  different  regions   of  Russia  and Belarus is described.  The results of the meetings and the work, shops  with the leaders  of a number of canning plants are summa, rized.